Promotions and Team Building for Marketing Campaigns - Sodoma, Ruslana; Kovalchuk, Oleg; Sadura, Oksana; Popadynets, Nazariy (Journal of Vasyl Stefanyk Precarpathian National University, 2023)
The article analyzes in detail the main aspects of promotional marketing in team building. Team building is very important for marketing campaigns as it allows for the efficient completion of tasks and the achievement of set goals. The main purpose of the article is based on the evaluation of the effectiveness of marketing communications using the Yule model and the creation of a framework for the business modeling of the brand, since having a ready-made business model structure, one can describe the cost structure, which will reflect the key actions and all resources for investment in brand development. The article summarizes the main advantages and disadvantages of promotions and highlights the main consequences of the war for Ukrainian brands. The main reason for team building is that marketing campaigns usually require work with different specialists such as marketers, designers, copywriters, analysts, etc. Therefore, project teams secure necessary communication and coordination between project participants to avoid misunderstandings and ensure the successful implementation of the project. Moreover, project teams can secure efficient management of resources such as time, budget, and other resources. This is especially important for marketing campaigns since they often have limited resources and shorter deadlines. Each team member contributes and performs specific tasks to achieve the campaign goal. Team building is an essential element in the successful implementation of marketing campaigns. It allows for efficient communication and coordination among project participants, resource management, and the achievement of successful results. Effective promotions can provide a company with a competitive advantage. This article discusses the main types of promotions, such as advertising, discounts, gifts, contests, loyalty, etc. An important aspect is choosing the right type of promotion depending on the target audience and the company's marketing goals. The criteria for team building, including the abilities and skills of the participants, leadership, communication, and collaboration, are also considered. The concept of business management implies that the company's management should constantly work to improve business processes, optimize the use of resources, and efficiently utilize personnel. In addition, business management includes the development and implementation of the company's development strategy, as well as control over its financial results.